2017
DOI: 10.1186/s12917-017-1082-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topical insulin on second-intention wound healing in the red-eared slider turtle (Trachemys scripta elegans) – a controlled study

Abstract: BackgroundCompared with mammals, wound healing in reptiles is characterized by reduced wound contraction and longer healing times. The aim of this study is to describe the clinical and histopathological effects of topical insulin on second-intention healing of experimentally induced wounds in skin without dermal bony plates of Trachemys scripta elegans exposed to daily variations in ambient temperature and in an aquatic environment. Forty-four healthy adult females were assigned to two groups: Group 1 (n = 24)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…At day 28, ozone-treated wounds achieved a 19.01% greater reduction in mean wound size. The magnitude of this difference is lower than the 24.26% obtained in a similarly designed study using topical insulin [ 14 ]. Although wound contraction is not a major feature of second-intention wound healing in reptiles, it is an objective outcome used in most studies and the significantly higher wound contraction of the ozone-treated wounds may be an important finding bearing in mind the limited wound contraction reported in reptiles.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…At day 28, ozone-treated wounds achieved a 19.01% greater reduction in mean wound size. The magnitude of this difference is lower than the 24.26% obtained in a similarly designed study using topical insulin [ 14 ]. Although wound contraction is not a major feature of second-intention wound healing in reptiles, it is an objective outcome used in most studies and the significantly higher wound contraction of the ozone-treated wounds may be an important finding bearing in mind the limited wound contraction reported in reptiles.…”
Section: Discussioncontrasting
confidence: 58%
“…Samples were fixed in buffered 10% formaldehyde for 16 to 20 h, hemisectioned and processed to a paraffin-embedded state. Serial sections, 4 μm thick, were obtained from each block and stained to enable accurate evaluation of the wound healing process [ 11 14 ]. Thus, haematoxylin and eosin (HE) stain was used to evaluate microscopic features; methenamine silver (Gomori PAMS) to stain the basement membrane zone (BMZ); Masson's trichrome (TM) to evaluate the collagen fibres and extracellular matrix during the proliferative and remodelling phases; routine Gram stain was applied to evaluate bacterial proliferation.…”
Section: Methodsmentioning
confidence: 99%
“…26 Negrini et al (2017) also showed that insulin solution promotes healing in Trachemys scripta elegans with secondintention wounds. 27 In addition, Chen et al (2012) reported that closure time of excision wound was reduced from 7 to 5 days in insulin solution-treated animals, and this finding is associated with improved inflammatory response, reepithelization, and collagen remodeling in the wounds of the insulin-treated group. 17 Likewise, Lima et al (2012) reported that insulin cream (0.5 U/100 g) applied daily for 8 days reduces wound healing time in diabetic rats by reversing defective AKT and ERK signal transduction.…”
Section: Animal Studiesmentioning
confidence: 99%
“…A total of 6,363 articles were obtained through the above search strategy. After evaluating the qualification of the accredited research, a total of 13 studies, including four [16][17][18][19] clinical studies and nine [11,16,[20][21][22][23][24][25][26] animal studies, were found suitable to be involved in this review. The study flow chart is presented in Fig.…”
Section: Search Results and Details Of The Included Studiesmentioning
confidence: 99%